Cuantificación de macronutrientes en las semillas de salvia hispánica l. chía proveniente de Trujillo - Marquina Huaman, Silvia Madelaine (2017)
The objective of this research was to determine the macronutrient composition in the seeds of Salvia hispanica L. "Chia". macronutrient composition in the seeds of Salvia hispanica L. "Chia" was obtained The results obtained were: Humidity 83.5 g / 100g obtained by the gravimetric method of the stove; ash 5,92g / 100g obtained by the method of direct incineration; 2.1 g acidity (expressed as lactic acid) obtained by the method of acidimetry; Carbohydrates 24g / 100g obtained by the method of Fehling, 18 g protein / 100g obtained by the semi-micro Kjeldahl method, lipids 31.5g / 100g obtained by the method of Soxhlet. According to the results it is concluded that the seeds of Salvia hispanica L. "Chia" presents little fat, carbohydrates and an important protein content